Mandibular morphology in schizophrenia patients compared with non-psychiatric controls using digital panoramic radiography: a retrospective cross-sectional study from Istanbul, Türkiye - Hakan Bahadir; Nihal Yetįmoğlu; Özlem Oflezer; Murat Erkiran (BMC, 2024)
Abstract Background Schizophrenia is a chronic severe mental disorder characterized by impairment in cognition, emotion, perception, and other aspects of behavior. In light of the association of craniofacial dysmorphology with schizophrenia, mandibular morphology may provide clues about the role of neurodevelopment in the pathophysiology of schizophrenia. This retrospective cross-sectional study aimed to compare the mandibular morphology of patients with schizophrenia with controls using digital panoramic radiography (DPR). Methods 302 recorded diagnostic panoramic images obtained from 143 schizophrenia patients (98 males, 45 females), and 159 controls (73 males, 86 females), aged 18-45 years, were evaluated. Seven mandibular measurements consisting of ramus height, condylar height, gonial angle, antegonial angle, antegonial notch depth, ramal notch depth and bigonial width were measured from the DPRs in a double-blinded manner. Bivariate comparisons were carried out using the Independent t-test and Mann-Whitney U test. Logistic regression analysis was used for multivariate comparisons. Results Linear measurements were higher while angular measurements were lower in schizophrenia patients. Regression analyses indicated that female patients had greater ramus height (OR = 1.243; P = 0.001), condylar height (OR = 1.463; P = 0.048) and bigonial width (OR = 1.082; P < 0.001); male patients had greater ramus heights (OR = 1.216; P = 0.001) and bigonial width (OR = 1.076; P < 0.001) as well as lower antegonial angle (OR = 0.908; P = 0.012) compared to their respective controls. Conclusion Quantitative differences in mandibular morphology in schizophrenia patients versus controls deserve attention and corroborate with the concept of abnormal neurodevelopment in schizophrenia.